Padrões de riqueza e diversidade de peixes de riacho e a relação local-regional, bacia Tocantins-Araguaia, região Centro-Oeste - CARNEIRO, Luciano Lajovic (2011)
This research aims to assess the fish biodiversity of the streams of the Tocantins and Araguaia basin and test the relative influence of local and regional processes in determining local species richness by examining the relationship between local species richness and regional species richness. For this purpose were sampled 18 streams in the basin of the Araguaia River and 16 streams in the basin of the Tocantins River in the state of Goiás using trawls. For analysis of richness observed was used and linear regression to assess the relationship of local and regional richness. The average value of diversity index of Shannon-Wiener were similar (p> 0.098) to the streams of the Tocantins (H`= 1.784) and Araguaia (H` = 2.254), uniformity also showed similar values (p> 0.962), but the average richness values were different (p = 0.039) for the basin of Tocantins S = 7.12 and S = 11.38 for Araguaia basin. Species richness of the Araguaia streams was strongly related to regional richness (r² = 0.826, p <0.0001) indicating a linear relationship and suggesting that local assemblies are unsaturated. For Tocantins streams was obtained a weak relationship (r²= 0.251, p = 0.047) and it was not possible to infer the shape of the relationship, several factors may be involved in the result. The diversity index was not an efficient descriptor of biodiversity, the test of the relationship between local and regional richness is a good predictor of ecological processes that influence species richness, has the disadvantage of the need to obtain a large amount of data.